2013
DOI: 10.5688/ajpe777145
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoeconomics Education in US Colleges and Schools of Pharmacy

Abstract: Objective. To determine the extent of pharmacoeconomics education in US colleges and schools of pharmacy provided to doctor of pharmacy (PharmD) students in 2011.Methods. E-mails requesting syllabi and information about courses covering pharmacoeconomic topics were sent to all US colleges and schools of pharmacy from which PharmD students had graduated in 2011 (n5103). Results. Of 87 responding pharmacy colleges and schools, 85 provided pharmacoeconomics education in 2011. The number of hours dedicated to phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
1
14
0
2
Order By: Relevance
“…On the other hand, pharmacoeconomics education in the US is provided at almost all colleges and pharmacy schools. [30] According to the online retrieved curriculums, most of the included Arab countries located in North Africa (Morocco, Algeria, Libya) do not require schools to include pharmacoeconomic education at any level (partial/full or mandatory/elective). This may explain the low number of schools offering pharmacy baccalaureate programs and slo perhaps still utilizing the traditional pharmacy curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, pharmacoeconomics education in the US is provided at almost all colleges and pharmacy schools. [30] According to the online retrieved curriculums, most of the included Arab countries located in North Africa (Morocco, Algeria, Libya) do not require schools to include pharmacoeconomic education at any level (partial/full or mandatory/elective). This may explain the low number of schools offering pharmacy baccalaureate programs and slo perhaps still utilizing the traditional pharmacy curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is an increasing global demand for experts in the field of pharmaceutical outcomes and policy research (Rascati et al, 2004). These trends are driven by several studies which have unequivocally demonstrated the importance of including pharmacoeconomics, pharmacoepidemiology and outcomes research in formulary decision-making, disease management, therapeutic drug monitoring, and the assessment of safety and efficacy of different medications (Reddy et al, 2008, Makhinova and Rascati, 2013, Nwokeji et al, 2007). Pharmacoeconomics also gains importance due to a continuously increasing pressure on the healthcare budgets in most countries (van Oostenbruggen et al, 2005), an issue potentiated in impoverished regions of the world (Desai et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The survey also found a variation in the number of teaching hours and topics covered in the PharmD curriculum. 8 In 2008 survey, among the 90 institutions of pharmacy that completed the survey, 7 had no teachers for pharmacoeconomics. 9 Their earliest survey performed in 1997 showed that sixty-three (80 percent) schools offered pharmacoeconomics education at the BS and/ or PharmD level.…”
Section: Usmentioning
confidence: 99%